Development of a Tool for Programming the Machining Instructions in a CAM Environment (Global Journals of Research in Engineering, 2013)
The objective of this paper is the develeppement a tool for programming the machining instructions in a CAM environment. To help the NC programming of all addresses, it was developed a module contributing to the adaptation of CN addresses for different languages FANUC, FAGOR, NUM, SINUMERIK and EIA, turning and milling. This module serves several functions. The first function is to seek designation of preparatory functions after selecting the command "/ operation" and "G-code" and the auxiliary functions. The second function allows the identification of all NC addresses with writing syntax desired codes. The third function is to automate the calculation of various parameters of cutting. The fourth function is devoted to the simulation programs.
Keywords: CAM; Tool; programming; here